The Impact and Prospects of AI-Generated Content in Educational Environments - Liu, Dingshan (Transactions on Computer Science and Intelligent Systems Research, 2024)
This paper examines the impact and emerging prospects of generative artificial intelligence (AI) content creation (AIGC) within the educational sector. As AI technology continues to evolve rapidly, the potential for AIGC to revolutionize educational practices has garnered significant interest and scholarly focus. AIGC is proving instrumental in developing customized educational content, facilitating personalized learning experiences, and enhancing assessment methods. These capabilities have the potential to significantly boost teaching efficiency and elevate student outcomes. Nonetheless, the integration of AIGC also poses several challenges, including concerns over academic integrity, shifts in the instructional roles of educators, and issues related to data privacy and ethical considerations. This analysis delves into the current applications of AIGC in education, discussing technological trends, innovations in educational models, and strategic policy recommendations. It underscores the necessity for future research to concentrate on evaluating the practical effects of AIGC, addressing potential drawbacks, and ensuring its responsible growth in educational settings.